Turning natural products into insecticide candidates: Design and semisynthesis of novel fraxinellone-based N-(1, 3-thiazol-2-yl)carboxamides against two crop-threatening insect pests. Issue 2 (15th January 2019) - Guo, Yong; Fan, Jiangping; Zhang, Qian; Bao, Chongnan; Liu, Zhiyan; Yang, Ruige
Graphical abstract: Highlights: 25 novel N -(1, 3-thiazol-2-yl)carboxamides of fraxinellone were prepared. Compounds6b and6i exhibited potent insecticidal activities against two insect pests. Compound6b and6i showed low cytotoxicity to noncancerous mammalian cells. The interesting structure–activity relationships were also discussed. Abstract: To improve the insecticidal activities of fraxinellone, two series of fraxinellone-based N -(1, 3-thiazol-2-yl)carboxamides containing 25 compounds were prepared by structural modification. Their structures were determined by melting point, optical rotation, IR, 1 H NMR and ESI-MS. The steric configurations of compounds6i, 7d and7i were unambiguously confirmed by X-ray diffraction further. The bioassay showed that compounds6b and6i exhibited more potent larvicidal and growth inhibitory activities against Plutella xylostella Linnaeus and Mythimna separata Walker, respectively. Moreover, compounds6b and6i also displayed low cytotoxicity to noncancerous mammalian cells. The structure–activity relationships (SARs) of all target compounds were also observed.